2020
DOI: 10.1021/acs.orglett.0c03530
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Hydrodefluorination with Silane as the Directing and Reducing Group

Abstract: We describe herein an efficient and selective Ru-catalyzed intramolecular HDF directed by a silyl group, which is readily installed, and removable and transformable following the HDF reaction. The hydrosilyl group in polyfluoroaryl silane acts not only as the directing group but also as the internal reductant, enabling precise control of the ortho-selectivity and avoiding overdefluorination. Mechanistic studies reveal a plausible catalytic cycle involving a Ru­(IV)–aryne intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…In 2020, Huang et al reported that the Ru-pincer complex catalyzed ortho-selective hydrodefluorination of polyfluoroarenes in which an in-built hydrosilane moiety plays a pivotal role as a directing group as well as a reductant (Scheme 20a). 85 The (pincer)Ru− H species initiates the catalysis via the oxidative addition of a H−Si to form a Ru(IV) species, 77 (Scheme 20b). The migration of an ortho F atom to a Si center, followed by C−Si bond cleavage, gives the aryne−Ru(IV) intermediate 78, which then undergoes hydrometalation or silylmetalation to form 79 or 79′.…”
Section: Directed C−f Bond Activation Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Huang et al reported that the Ru-pincer complex catalyzed ortho-selective hydrodefluorination of polyfluoroarenes in which an in-built hydrosilane moiety plays a pivotal role as a directing group as well as a reductant (Scheme 20a). 85 The (pincer)Ru− H species initiates the catalysis via the oxidative addition of a H−Si to form a Ru(IV) species, 77 (Scheme 20b). The migration of an ortho F atom to a Si center, followed by C−Si bond cleavage, gives the aryne−Ru(IV) intermediate 78, which then undergoes hydrometalation or silylmetalation to form 79 or 79′.…”
Section: Directed C−f Bond Activation Inmentioning
confidence: 99%
“…In 2020, Huang et al reported that the Ru-pincer complex catalyzed ortho -selective hydrodefluorination of polyfluoroarenes in which an in-built hydrosilane moiety plays a pivotal role as a directing group as well as a reductant (Scheme a) . The (pincer)­Ru–H species initiates the catalysis via the oxidative addition of a H–Si to form a Ru­(IV) species, 77 (Scheme b).…”
Section: Directed C–f Bond Activation In Polyfluorinated Compoundsmentioning
confidence: 99%
“…An increasing number of applications of fluoroaryl-containing compounds in materials, [1] agrochemicals, [2] and pharmaceuticals [3] encourages the development of new strategies to synthesize such classes of compounds. Procedures to functionalize fluorinated arenes and the conversion of fluoroarenes into more complex organic molecules has been reported using fluoroaryl boronates, [4,5] magnesium, [6] lithium, [7,8] zinc, [9,10] or silicon reagents, [11] as well as halides, [12] and carboxylic acids. [13] However, the development of synthetic procedures to modify fluoroarenes via direct CÀ F [14] or CÀ H [15] functionalization is highly desirable as it decreases the number of synthetic steps, waste, cost, and energy usage.…”
Section: Introductionmentioning
confidence: 99%
“…Low-valent transition-metal complexes are commonly used to activate aromatic C­(sp 2 )–F bonds. , Using transition-metal complexes, e.g., Pd, Ni, Ru, and Fe, in the presence of silane reductants, fluoroarenes can proceed to hydrodefluorination. For aliphatic C­(sp 3 )–F bond activation, strong main-group electrophiles, particularly silylium ions, R 3 Si + , were employed to heterolytically cleave the C–F bond .…”
Section: Introductionmentioning
confidence: 99%